Compressive Strength of Cement Mortar with Nano ZnO as Admixture - Mohan Kantharia, Pankaj Kumar Mishra (International Journal of Advanced Science and Technology, 2020)
Compressive strength is the main characteristic of cement concrete and mortar. In this investigation cement mortar is tested with nano Zinc oxide. The percentage of Nano particle is taken 0.5, 1.0, 1.5 and 2.0% of weight of cement. Compressive strength is determined after curing of 3,7,14, 28 days of curing. It is found that more percentage of Nano materials is not beneficial for compressive strength, but lower percentage is giving slightly higher strength. More percentage of ZnO makes Zinc hydroxide compound around the CSH gel particles which is not beneficial for compressive strength.